A Novel Kinetic Method to Measure Apparent Solubility Product of Bulk Human Enamel - Hassanali, Linda; Wong, Ferranti S.; Lynch, Richard J. M.; Anderson, Paul (Frontiers in Physiology, 2017)
Introduction Tooth enamel mineral loss is influenced by its solubility product value, which is fundamental to the understanding of de- and remineralisation resulting from a carious or erosive challenge. Published pKsp values for human enamel and hydroxyapatite range from 110-126 suggesting a heterogeneous nature of enamel solubility. However, this range of values may also result from the variety of methods used, e.g. some authors reporting values for suspensions of enamel powder and others for bulk enamel. The aim of this study was to develop a method to measure the solubility of bulk human enamel under controlled in vitro conditions simulating demineralisation behaviour of enamel within the oral environment using scanning microradiography (SMR). SMR was used to monitor real-time changes in enamel demineralisation rates at increasing calcium concentrations in a caries simulating demineralisation solution until the concentration at which thermodynamic equilibrium between enamel and solution was achieved. Method: 2 mm thick caries free erupted human enamel slabs with the natural buccal surfaces exposed were placed in SMR cells exposed to circulating caries-simulating 2.0 L 0.1 M pH=4.0 acetic acid, at 25ºC. SMR was used to continuously measure in real-time the decrease in mineral mass during the demineralisation at 5 different points from on each slab. Demineralisation rates were calculated from a linear regression curve of projected mineral mass against demineralisation time. Changes in the demineralisation rates were monitored following a series of successive increases in calcium (and phosphate at hydroxyapatite stoichiometric ratios of Ca:P 1.67) were added to the demineralising solution, until demineralisation ceased. The pH was maintained constant throughout. Results: Demineralisation halted when the calcium concentration was 30mM. At higher calcium concentrations, mineral deposition (remineralisation) occurred. By comparison with results from speciation software calculations for the calcium phosphate ternary system, this result suggests that the bulk solubility product of enamel (pKspBEnamel) under the conditions used is 121. Discussion: The pKspBEnamel under these conditions was lower than many previous reported values, and much closer to those previously reported for HAp. However, this is a bulk value, and does not reflect that enamel is a heterogeneous material, nor the influence of ionic